Symbolika obrazu «Alegorii Bożej Opatrzności» z klasztoru Sióstr Wizytek w Krakowie - Moisan-Jablonski, Christine (Saeculum Christianum. Pismo Historyczne, 2016)
There is an eighteenth-century painting depicting Allegory of Divine Providence in the convent of the Sisters of the Visitation in Kraków. The iconography is unique. In addition to figures of people and animals abandoning themselves to the care of Divine Providence, it also shows the seven archangels. Although the Catholic Church only recognizes three Archangels (Gabriel, Michael and Raphael), portrayals of seven archangels appeared in European art at the end of sixteenth century and in the seventeenth and eighteenth centuries, which also showed figures representing Uriel, Barachiel, Sealtiel and Jehudiel. The Reverend Ignacy Tłuczyński also mentions them in a book—on to the subject of angels and the care which angels and heavenly spirits provide to people—published in Kraków in 1677. It would be impossible to have a full understanding of the message conveyed in the Kraków painting without having knowledge of Polish eighteenth-century religious songs devoted to Divine Providence. The dominant motif—which also appears on other Polish paintings depicting Divine Providence—is the portrayal of people and animals together, to whom Providence is offering various gifts.